Visual Outcome after Cataract Surgery in a Tertiary Eye Hospital in Southern Region of Bangladesh - Islam, Mohammad Ariful Islam; Rain, Md Zinnu Rain; Mridha, Md Zan E Alam; Azad, Abul Kalam; Mamun, Al; Majumder, Md Yousuf (Central Medical College Journal, 2024)
Background: Vision is a very important sense for human life which is directly related with education, performance of work and quality of life. Worldwide cataract is considered one of the leading causes of blindness and visual impairment. Cataract surgery is one of the most commonly performed procedures in ophthalmology. Cataract extraction with intraocular lens (IOL) implantation is the only surgical approach available mostly in developing countries. Objective: This study aimed to evaluate the visual outcome who have had their cataract surgery in a tertiary level eye hospital. Method: Prospective interventional study was conducted from 1st January 2019 to 31st December 2019 at Sheikh Fazilatunnesa Mujib Eye Hospital & Training Institute (SFMEHTI), Gopalganj. It was a hospital based study of consecutive cataract-operated patients who had age-related cataract with vision 6/24 or less before surgery. For surgery all the patients were evaluated including their relevant investigations with trained ophthalmologist and allowed as fit for surgery. Total 8776 patients who admitted in this hospital and fulfill the eligibility criteria were included in this study. Patients in age of 40 - 80 years were included in the study. The most common procedure was phacoemulsification (PE) with posterior chamber intraocular lens (PCIOL) 4704 (53.6%) followed by small incision cataract surgery (SICS) with posterior chamber intraocular lens (PCIOL) implantation, operated in4072 (46.4%) eyes. Most of the surgery was done by well-trained ophthalmologists; whereas few surgeries were done by young ophthalmologists under the supervision of senior ophthalmologist. Result: Among 8776 patients operated, the most common group was 40-60 years (65.5%). The mean age of the patients was 60.47 years. Male patients were more (52.8%). In post cataract surgery patients, 5967 (68%) eyes had presenting vision >6/18. Visual acuity (VA) <6/60 was found in 176 (2%) eyes. In 8600 (98%) eyes visual acuity (VA) was improved after best correction. Poor visual outcome was significantly associated with the patients who were in older age, gender female, literacy, hearing impairment and SICS& PE surgery techniques. Conclusion: This study observed that good visual acuity can achieved in cataract surgery. More attention should be given towards monitoring of cataract surgical outcomes and correction of refractive error after surgery. It is also important to meet the WHO standard of visual outcome after cataract surgery. Central Medical College Journal Vol 8 No 1 January 2024 Page: 7-11